The body in mind : medical imagery in Sophocles - Allan, W (Franz Steiner Verlag, 2014)
This article analyses the depiction of mental and physical pain in Sophoclean tragedy, showing how Sophocles uses medical imagery to explore fundamental problems in the personality and behaviour of his protagonists. It argues that the concentration of medical language at certain moments in particular plays not only makes the scenes more graphic and credible, but also articulates the causes and consequences of the characters' predicament. Particular attention is given to Ajax's delusions and maddening shame, Heracles' agony and Deianeira's mistake, and Philoctetes' intransigence and resentment. Sophocles' sustained and detailed engagement with medical language and thought reveals him to be (no less than Aeschylus or Euripides) deeply interested in the wider intellectual and scientific issues of his time.